Britain in the Twentieth Century - Cawood, Ian. (London ; New York : Routledge, 2004)
Britain in the Twentieth Century is a new approach to teaching and learning twentieth century British history at A level. It meets the needs of teachers and students studying for today's revised AS and A2 exams. In a unique style, Britain in the Twentieth Century focuses on the key topics within the period. Each topic is then comprehensively explored to provide background, essay writing advice and examples, source work and historical skills. From 1900 to the new millennium, the key topics featured include:* Britain in a new century, 1900-1914* the First.
Introduction to Britain in the twentieth century -- Britain in a new century, 1900-1914 -- The impact of the First World War, 1914-1918 -- Inter-war domestic problems, 1918-1939 -- British foreign policy between the wars, 1918-1939 -- Britain and the Second World War, 1939-1945 -- The age of consensus: domestic affairs, 1945-1979 -- The wind of change: foreign and colonial policy, 1945-1979 -- Social and economic change, 1945-1979 -- Towards the millennium, 1979-2000 -- Conclusion: end of the period survey.
Includes bibliographical references (pages 458-462) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Great Britain -- History -- 20th century; Great Britain -- History -- 20th century; Grande-Bretagne -- Histoire -- 20e siècle.; JUVENILE NONFICTION -- General; Great Britain; Großbritannien; 1900-1999; History